Comorbidity has no impact on unplanned discharge or functional gains in persons with dysvascular amputation - Raymond Cheng; Sean Smith; Claire Z. Kalpakjian (Medical Journals Sweden, 2019)
Objective: To examine how factors associated with infection, organ failure, poor wound healing, or indices of chronic vascular disease are associated with unplanned transfers and functional gains in a population of dysvascular amputees during inpatient rehabilitation. Design: Cross-sectional. Setting: Inpatient rehabilitation unit at an academic medical centre. Patients: A total of 118 patients with new, dysvascular, lower-extremity, amputation participating in inpatient rehabilitation. Methods: Logistic regression and indices of change (minimal detectable change; MDC90), standardized response mean and effect size were used to examine the risks of unplanned transfer and functional change. Main outcome measurements: Rate of unplanned transfers from rehabilitation, and Functional Independence Measure (FIM). Results: Out of the total of 118 patients 19 had unplanned transfers due to medical complications. Age, creatinine, haemoglobin, white blood cell count, haemodialysis, wound vacuum device use, intravenous antibiotic use, or previous amputations were not independently associated with unplanned transfers, motor FIM change or efficiency. The MDC90 for motor FIM was 17.84, with 21.2% of patients exceeding this value; standardized response mean and effect size were large (1.03 and 1.39, respectively). Conclusion: This study suggests that the presence of comorbidities in a population of dysvascular amputees participating in inpatient rehabilitation did not increase the risk of unplanned transfers or affect FIM gains.